2010
DOI: 10.1590/s0004-282x2010000100005
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and auditory behavioral evaluation of individuals with left temporal lobe epilepsy

Abstract: The purpose of this study was to determine the repercussions of left temporal lobe epilepsy (TLE) for subjects with left mesial temporal sclerosis (LMTS) in relation to the behavioral testDichotic Digits Test (DDT), event-related potential (P300), and to compare the two temporal lobes in terms of P300 latency and amplitude. We studied 12 subjects with LMTS and 12 control subjects without LMTS. Relationships between P300 latency and P300 amplitude at sites C3A1,C3A2,C4A1, and C4A2, together with DDT results, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
(23 reference statements)
0
12
0
Order By: Relevance
“…This result suggests that the neural function of MTS patients does not contribute the neural synchrony necessary for the detection of subtle electrophysiological events. This finding was further supported by studies showing electrophysiologic abnormalities in event-related potentials (ERPs) recorded from patients with MTS 29 , which were not observed using a similar paradigm in the visual modality 30 .…”
Section: Discussionmentioning
confidence: 55%
“…This result suggests that the neural function of MTS patients does not contribute the neural synchrony necessary for the detection of subtle electrophysiological events. This finding was further supported by studies showing electrophysiologic abnormalities in event-related potentials (ERPs) recorded from patients with MTS 29 , which were not observed using a similar paradigm in the visual modality 30 .…”
Section: Discussionmentioning
confidence: 55%
“…Our results are in accordance with previous studies with centrally recorded P300s (Fukai et al ., ; Chen et al ., ; Rocha et al ., ). Other studies have focused on limbic P300, showing reduced amplitudes and prolonged latencies, which is similar to our findings for centrally recorded P300 (Puce et al ., ; Nelson et al ., ; Psatta and Matei, ; Grunwald et al ., ; Rocha et al ., ). A possible explanation for a diffuse P300 disturbance is the presence of a diffuse‐projecting P300 generator, most likely also involving temporal regions of the brain (Polich, ; Duncan et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Individuals with cortical lesions outside the temporal lobe do not exhibit inferior performance on the DD Test compared with control groups 30 . Studies on patients with temporal lobe epilepsy have also indicated a worse performance on the DD Test in both ears compared with control groups 31 , 32 . These studies demonstrate the importance of the temporal lobe in sound processing during a dichotic task.…”
Section: Discussionmentioning
confidence: 99%